Molecular phylogenetics, systematics, reproductive safeguarding and chromosome evolution of the genus Lachenalia (Asparagaceae: Scilloideae) - Duncan, Graham (Department of Biological Sciences, 2025)
The genus Lachenalia, comprising 142 species and belonging to the monocotyledonous family Asparagaceae, is morphologically diverse and the most species-rich member of the family in southern Africa. Past attempts to infer a well-resolved and robustly supported phylogenetic tree using Sanger sequencing of candidate loci and/or morphological characters have been largely unsuccessful. A new phylogenetic hypothesis for Lachenalia is presented, using multi-locus sequence data sampled from living material of 132 taxa via maximum likelihood and coalescent-based species tree estimation (ASTRAL), as applied to 378 hybrid enrichment loci. This resolves species-level relationships with good support, thereby providing a sound basis for a new infrageneric classification, revealing several new taxa which are described here, and, most importantly, establishing a solid framework for downstream evolutionary studies. A dated version of the multi-locus phylogenetic tree is employed here to test the hypothesis that pollen limitation, resulting from a low abundance of insect pollinators, promotes the evolution of reproductive safeguarding traits (self compatibility, autonomous selfing, bird pollination and clonal propagation) in low insect abundance contexts (i.e., infertile fynbos heathland, and species which flower outside of the austral spring season). Ancestral state reconstructions identify an association with non-fynbos vegetation and spring-flowering as ancestral, with the transition to fynbos and non-spring flowering having taken place multiple times. Ordinary and phylogenetic regressions suggest that bird pollination and self-compatibility are selected for in fynbos and in non-spring flowering lineages, with autofertility being positively associated with non-spring flowering. These patterns support interpretation of these traits as reproductive safeguarding adaptations under reduced insect pollinator abundance. The dated multilocus phylogenetic tree is also used to explore the evolution of cytotype and genome size in Lachenalia. Novel genome size data for 124 species are reported and reconciled with existing karyotype data to show that genome size variation is largely a product of polyploidization, with polyploidy yielding lineages that are mostly short-lived and recent. By contrast, dysploid change, which is frequent in Lachenalia but has little impact on genome size, yields lineages that persist through time and diversify. Lachenalia describes a dysploid reduction series with a high ancestral base number.